2009
DOI: 10.1073/pnas.0810563106
|View full text |Cite
|
Sign up to set email alerts
|

Rubisco in complex with Rubisco large subunit methyltransferase

Abstract: SET domain protein lysine methyltransferases (PKMT) are a structurally unique class of enzymes that catalyze the specific methylation of lysine residues in a number of different substrates. Especially histone-specific SET domain PKMTs have received widespread attention because of their roles in the regulation of epigenetic gene expression and the development of some cancers. Rubisco large subunit methyltransferase (RLSMT) is a chloroplastlocalized SET domain PKMT responsible for the formation of trimethyl-lysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…Also, the unmethylated status of Rubisco in Arabidopsis and other species like spinach or wheat does not reflect sequence divergence of LS around the Lys-14 methylation site (see supplemental Fig. 4) or the residues mediating the interaction with the methyltransferase (23). The structure of the active site of PsLSMT indicated that the LS Rubisco and AdoMet substrates bind to separate clefts connected by a pore large enough to accommodate the transfer of methyl groups to Lys-14 (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the unmethylated status of Rubisco in Arabidopsis and other species like spinach or wheat does not reflect sequence divergence of LS around the Lys-14 methylation site (see supplemental Fig. 4) or the residues mediating the interaction with the methyltransferase (23). The structure of the active site of PsLSMT indicated that the LS Rubisco and AdoMet substrates bind to separate clefts connected by a pore large enough to accommodate the transfer of methyl groups to Lys-14 (16).…”
Section: Discussionmentioning
confidence: 99%
“…This protein, referred to as AtLSMT-L for Arabidopsis LSMTlike, shares 62% sequence identity (plus 15% conservative changes) with PsLSMT. Hence, both the N-terminal located catalytic SET domain and the C-terminal lobe that forms extensive contacts with the LS Rubisco substrate are highly conserved between both proteins (23). AtLSMT-L is a 482-residue and 54.6-kDa protein harboring a predicted chloroplastic transit peptide.…”
Section: Atlsmt-l Is Dispensable For Arabidopsis Growth In Ambientmentioning
confidence: 99%
See 1 more Smart Citation
“…of L-subunit pairs in L 8 S 8 Rubisco but not the S-subunits (Raunser et al, 2009), suggesting that trimethylation of Lys-14 occurs after L 2 assembly (see below) and prior to S-subunit assembly (Fig. 5).…”
Section: Rubisco and Its Interactions With Other Proteins Rubisco Expmentioning
confidence: 95%
“…RLSMT was shown to exist in complex with Rubisco (Raunser et al, 2009) in which the Lys-14 is trimethylated in several species belonging to the Fabaceae, Solanaceae, and Cucurbitaceae families but not in wheat (Triticum aestivum), spinach (Spinacia oleracea), or Arabidopsis (Houtz et al, 1992;Mininno et al, 2012). Despite numerous studies, the effects of Lys-14 trimethylation of RBCL have not been defined, and RLSMT knockdown plants do not show marked defects in growth and CO 2 assimilation (Mininno et al, 2012).…”
Section: Lys and Arg Methylationmentioning
confidence: 99%